Hyper-lattice Algebraic Model for Data Warehousing - Sen, Soumya; Cortesi, Agostino; Chaki, Nabendu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents Hyper-lattice, a new algebraic model for partially ordered sets, and an alternative to lattice. The authors analyze some of the shortcomings of conventional lattice structure and propose a novel algebraic structure in the form of Hyper-lattice to overcome problems with lattice. They establish how Hyper-lattice supports dynamic insertion of elements in a partial order set with a partial hierarchy between the set members. The authors present the characteristics and the different properties, showing how propositions and lemmas formalize Hyper-lattice as a new algebraic structure.
Hyper Lattice -- Applications of Hyper-Lattice in Real Life -- Generating Co-Operative Queries over Concept Hierarchies -- Conclusions.
Keywords: Telecommunication; Data structures (Computer science).; Information theory; Algebra; Statistics .; Communications Engineering, Networks; Data Structures and Information Theory; Order, Lattices, Ordered Algebraic Structures; Statistics in Engineering, Physics, Computer Science, Chemistry and Earth Sciences